Panoramic Observation of Crystalline Lenses with 25 MHz Ultrasonography - Wenwen Xue; Haidong Zou (Journal of Ophthalmology)
Purpose. To visualize and assess in vivo the age-related changes in crystalline lens size and contour. Methods. Seventy-nine healthy volunteers, 39 females and 40 males, with a mean age of 41.53 + 11.32 years (range: 21 to 60 years) were enrolled in this study. The axial lens thickness (ALT), equatorial lens diameter (ELD), and anterior (Ra) and posterior (Rp) lens surface radii of curvatures of the subjects’ left eyes were measured with a 25 MHz ultrasound probe. Results. The mean ALT and ELD were 4.178 mm + 0.288 mm and 9.209 mm + 0.214 mm, respectively. There was a statistically significant increase in both ALT (slope = 11 μm/year, r = 0.88, p<0.01) and ELD (slope = 6 μm/year, r = 0.60, p<0.01) with age. Ra negatively correlated, and Rp did not change with age. Conclusion. There were no statistically significant relationships between any studied values and gender. Independent of gender, the lens grows equatorially and axially with age while its central anterior lens surface steepens and its posterior central surface curvature does not change.